PENGARUH MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS KELAS IV SD - Sipriana, Jaenita Dwi; Siti Patonah; Intan Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Think Pair Share cooperative learning model on students' learning outcomes in IPAS subjects in grade IV of SD Negeri Karaban 01 Pati. The low learning outcomes of students were caused by teacher-centered learning that made students passive. This research used a quantitative method with a True Experimental Design in the form of a Pretest-Posttest Control Group Design involving two classes: an experimental class (IV-C, n=20) and a control class (IV-B, n=26). Data were collected through pretest and posttest instruments consisting of 20 multiple choice items that had been validated and declared reliable (r11 = 0.84). The results showed that the average score of the experimental class increased from 58.75 (pretest) to 87 (posttest), while the control class increased from 47.25 to 67.25. The hypothesis test using the Independent Sample t-test obtained a significance value of 0.000 < 0.05 and t-count of 6.285 > t-table of 2.015. This indicates that there is a significant effect of the Think Pair Share cooperative learning model on students' learning outcomes in IPAS subjects in grade IV of SD Negeri Karaban 01 Pati.